Data hiding in the FAT family file system structure - Shekhanin, K.Yu.; Kolhatin, A.O.; Demenko, E.E.; Kuznetsov, A.A. (Radiotekhnika, 2018)
Methods of technical steganography, namely, those ones based on information messages hiding in the structure of the FAT family file system are studied. The basic method based on changing the numbering of cover files clusters is considered, its advantages and disadvantages are researched. An improved method is proposed that makes it possible to increase significantly the hidden data size. The results of the comparative analysis of hiding data in the structure of the FAT family file system are given.